2021
DOI: 10.21608/jbaar.2021.177577
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in some Egyptian Zea mexicana genotypes based on RAPD and AFLP markers

Abstract: Maize-Teosinte hybrids are of significant interest to maize breeders as a resource of genetic diversity during the maize domestication process as a genetic pool for maize improvement. This study examines the genetic diversity and population structure of 16 Zea mexicana populations which are currently active in Zea breeding programs in Egypt using Random Amplified Polymorphic DNA (RAPD) and Amplified Fragment Length Polymorphism (AFLP) markers. RAPD analysis (14 primers) produced 141 bands; out of which, 102 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Data presented in Table (1) showed that there are significant differences at 0.05 probability levels among the seven genotypes over the two seasons and the three cuts for all studied traits i.e., plant height, stem diameter, fresh yield, dry yield and their total fresh and dry yields. These results were in line with those of Wright (1935), Radwan and Zayed (2021) and El-Gaafarey et al (2023).…”
Section: Results and Discussion A-forage Experiment: Analysis Of Vari...supporting
confidence: 90%
“…Data presented in Table (1) showed that there are significant differences at 0.05 probability levels among the seven genotypes over the two seasons and the three cuts for all studied traits i.e., plant height, stem diameter, fresh yield, dry yield and their total fresh and dry yields. These results were in line with those of Wright (1935), Radwan and Zayed (2021) and El-Gaafarey et al (2023).…”
Section: Results and Discussion A-forage Experiment: Analysis Of Vari...supporting
confidence: 90%
“…They constructed a dendrogram in which 3 main clusters emerged. On the other hand, the authors Radwan et al (2021), Al-Obaidi et al (2018, Ristic et al (2013) and Sharawy et al (2011) detected a higher number of DNA fragments per primer and a higher percentage of polymorphism. Radwan et al (2021) examined the genetic diversity of 16 Zea mexicana populations.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, the authors Radwan et al (2021), Al-Obaidi et al (2018, Ristic et al (2013) and Sharawy et al (2011) detected a higher number of DNA fragments per primer and a higher percentage of polymorphism. Radwan et al (2021) examined the genetic diversity of 16 Zea mexicana populations. 14 RADP primers amplified 141 DNA fragments (average of 10.1 bands per primer) out of which, 102 (72.3%) were polymorphic.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Data presented in Table 2 showed that there are highly significant differences among the seven genotypes at the first and second seasons (2020/2021) and the combined for all studied traits i.e plant height , stem diameter , fresh yield , dry yield at the three cuts in the two seasons and their total fresh and dry yields [18,19,20,21,22].…”
Section: Results and Dissectionmentioning
confidence: 99%